Construction and Characterization of a Cellulolytic Consortium Enriched from the Hindgut of Holotrichia parallela Larvae - Sheng, Ping (Int J Mol Sci, 2016)
Degradation of rice straw by cooperative microbial activities is at present the most attractive alternative to fuels and provides a basis for biomass conversion. The use of microbial consortia in the biodegradation of lignocelluloses could reduce problems such as incomplete synergistic enzymes, end-product inhibition, and so on. In this study, a cellulolytic microbial consortium was enriched from the hindgut of Holotrichia parallela larvae via continuous subcultivation (20 subcultures in total) under static conditions. The degradation ratio for rice straw was about 83.1% after three days of cultivation, indicating its strong cellulolytic activity. The diversity analysis results showed that the bacterial diversity and richness decreased during the consortium enrichment process, and the consortium enrichment process could lead to a significant enrichment of phyla Proteobacteria and Spirochaetes, classes Clostridia, Epsilonproteobacteria, and Betaproteobacteria, and genera Arcobacter, Treponema, Comamonas, and Clostridium. Some of these are well known as typical cellulolytic and hemicellulolytic microorganisms. Our results revealed that the microbial consortium identified herein is a potential candidate for use in the degradation of waste lignocellulosic biomass and further highlights the hindgut of the larvae as a reservoir of extensive and specific cellulolytic and hemicellulolytic microbes.